EVALUATION THE EFFECT OF APPLYING TRIZ METHOD ON CREATIVITY AND CONCEPTUALIZATION OF PRODUCT REDESIGN TRAINING BY INDUSTRIAL DESIGN STUDENTS - zahra merrikhpour; Vahid Choopankareh; shabnam samiei (آموزش مهندسی ایران, 2021)
In today’s world of design, creativity is an indispensable skill for designers and part of the educational process of industrial design students. One of the challenges in design education is to understand the concept of creativity for students and to guide them in using various approaches as an effective tool in design. The purpose of this study was to evaluate the quantitative and qualitative efficacy of using creative TRIZ method by industrial design students in product design based on 40 creative principles, its parameters and contradiction matrix. It is hypothesized that contrary to popular belief that most people feel that innovation is based on emotion and instinct, the main hypothesis in using this method is that creativity can be taught. To address this hypothesis, 20 undergraduate industrial design students at 6th semesters, were selected in the course of Creativity Project. They were asked to conceptualize and redesign their selected products based on 40 creativity principles and TRIZ Contradiction Matrix. The results show that applying the TRIZ method had a positive effect on students’ ability to analyze the product design process, leading to exact understanding of the problem, generating newer solutions, and enhancing creativity in ideation. Based on the obtained results, teaching this method and its practical application in the product design process is recommended. In this method, using the paper pen method in recording ideas made it possible to understand and make the method more effective.Keywords: Personal knowledge management, employability, students, engineering education, academi achivement.